2011
DOI: 10.1080/03004431003725386
|View full text |Cite
|
Sign up to set email alerts
|

Father residency and symptoms of ADHD: adult male involvement as a mediator

Abstract: The purpose of the current study was to investigate the association between fathers' involvement and the presence of later symptoms of attention deficit hyperactivity disorder (ADHD) in children. A community-based, nationally representative sample of children from the Early Childhood Longitudinal StudyKindergarten Cohort was utilised. Using a tripartite model, father involvement was investigated as a function of the time a father spent with the child and father's residency status. Structural equation modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…In addition to having less opportunity for mastery experiences associated with lower parenting self-efficacy, previous studies have shown that non-resident fathers tend to reduce contact with children over time (Bernard & Knitzer, 1999;Hamer, 2001;Smock & Manning, 1997). The decrease in interactions may interfere with the mediating role of a male adult on ADHD symptoms found in a study by Barnard-Brak et al (2010), resulting in a lack of association between father residency and ADHD symptoms. Hawkins, Amato, and King (2007) found that non-resident fathers are more likely to be involved in children's lives when the children are high-achieving and exhibit less behaviour problems.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In addition to having less opportunity for mastery experiences associated with lower parenting self-efficacy, previous studies have shown that non-resident fathers tend to reduce contact with children over time (Bernard & Knitzer, 1999;Hamer, 2001;Smock & Manning, 1997). The decrease in interactions may interfere with the mediating role of a male adult on ADHD symptoms found in a study by Barnard-Brak et al (2010), resulting in a lack of association between father residency and ADHD symptoms. Hawkins, Amato, and King (2007) found that non-resident fathers are more likely to be involved in children's lives when the children are high-achieving and exhibit less behaviour problems.…”
Section: Discussionmentioning
confidence: 79%
“…The relationship could be viewed as bidirectional, and the current models should not be used to infer causation. Male role models appear to provide some buffer for ADHD symptoms, as found by Barnard-Brak et al (2010), and if the resident father is involved from early childhood, then ADHD symptoms may not reach clinical levels in typically developing children.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Fathers (both resident and nonresident) do seem to play an important role in the developmental course of ADHD for their children (Barnard-Brak, To, Davis, & Thomson, 2011). Future quantitative research should consider whether the residency status of fathers may be associated with the frequency and duration of medication vacations for children with ADHD.…”
Section: Discussionmentioning
confidence: 99%